Preoperative atrial fibrillation is an independent risk factor for mid-term mortality after concomitant aortic valve replacement and coronary artery bypass graft surgery - Saxena, A.; Dinh, D.; Dimitriou, J.; Reid, Christopher; Smith, J.; Shardey, G.; Newcomb, A. (2013)
OBJECTIVES: Preoperative atrial fibrillation (PAF) has been associated with poorer early and mid-term outcomes after isolated valvular or coronary artery bypass graft surgery. Few studies, however, have evaluated the impact of PAF on early and mid-term outcomes after concomitant aortic valve replacement and coronary aortic bypass graft (AVR-CABG) surgery. METHODS: Data obtained prospectively between June 2001 and December 2009 by the Australian and New Zealand Society of Cardiac and Thoracic Surgeons National Cardiac Surgery Database Program was retrospectively analysed. Patients who underwent concomitant atrial arrhythmia surgery/ablation were excluded. Demographic and operative data were compared between patients undergoing concomitant AVR-CABG who presented with PAF and those who did not using chi-square and t-tests. The independent impact of PAF on 12 short-term complications and mid-term mortality was determined using binary logistic and Cox regression, respectively. RESULTS: Concomitant AVR-CABG surgery was performed in 2563 patients; 322 (12.6) presented with PAF. PAF patients were generally older (mean age 76 vs 74 years; P < 0.001) and presented more often with comorbidities including congestive heart failure, chronic pulmonary disease and cerebrovascular disease (all P < 0.05). PAF was associated with 30-day mortality on univariate analysis (P = 0.019) but not multivariate analysis (P = 0.53). The incidence of early complications was not significantly higher in the PAF group. PAF was independently associated with reduced mid-term survival (HR, 1.58; 95 CI, 1.14-2.19; P = 0.006). CONCLUSIONS: PAF is associated with reduced mid-term survival after concomitant AVR-CABG surgery. Patients with PAF undergoing AVR-CABG should be considered for a concomitant surgical ablation procedure.